2020
DOI: 10.3390/cancers12092581
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustion of Protective Heat Shock Response Induces Significant Tumor Damage by Apoptosis after Modulated Electro-Hyperthermia Treatment of Triple Negative Breast Cancer Isografts in Mice

Abstract: Modulated electro-hyperthermia (mEHT) is a complementary antitumor therapy applying capacitive radiofrequency at 13.56 MHz. Here we tested the efficiency of mEHT treatment in a BALB/c mouse isograft model using the firefly luciferase-transfected triple-negative breast cancer cell line, 4T1. Tumors inoculated orthotopically were treated twice using a novel ergonomic pole electrode and an improved mEHT device (LabEHY 200) at 0.7 ± 0.3 W for 30 min. Tumors were treated one, two, or three times every 48 h. Tumor g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(97 citation statements)
references
References 57 publications
8
81
0
Order By: Relevance
“…In our previous study we demonstrated that modulated electro-hyperthermia (mEHT) induced Hsp70 upregulation, and exhaustion of this defense mechanism resulted in apoptotic cell death of the mouse 4T1 triple negative breast cancer (TNBC) model. Hsp70 inhibition synergistically enhanced the tumor-killing effect of mEHT [ 1 ]. In the present study, our aim was to investigate the molecular effects of mEHT using multiplex methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study we demonstrated that modulated electro-hyperthermia (mEHT) induced Hsp70 upregulation, and exhaustion of this defense mechanism resulted in apoptotic cell death of the mouse 4T1 triple negative breast cancer (TNBC) model. Hsp70 inhibition synergistically enhanced the tumor-killing effect of mEHT [ 1 ]. In the present study, our aim was to investigate the molecular effects of mEHT using multiplex methods.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthermia decreases the activity of hypoxia-inducible factor 1 (HIF-1) and contributes to the vascular endothelial growth factor (VEGF)-mediated angiogenesis inhibition of Bevacizumab [ 5 ]. mEHT’s potential as a monotherapy is currently under investigation [ 1 , 6 ]. mEHT uses a 13.56 MHz frequency capacitively coupled electromagnetic field that transmits energy to the tumor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In colorectal adenocarcinoma models, mEHT treatment has been demonstrated to induce both caspase-dependent and caspase-independent AIF-mediated apoptosis [ 17 , 18 , 19 ]. In triple-negative breast cancer isografts, exhaustion of mEHT-induced heat shock response resulted in significant tumor damage via a caspase-dependent mechanism in mice [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of mEHT as a complementary therapy relies in its property to induce tumor-damage by direct cell killing, mediated by irreversible heat and cell stress and its tolerability by patients as it has almost no side-effects. In the recent years numerous papers have described the growth inhibiting effect of mEHT in various tumor types, mostly in preclinical mouse models ( 2 6 ). These results provide evidence that besides the direct cell killing, mEHT has an immunomodulatory effect supporting the anti-tumor immune response ( 3 , 4 , 7 ).…”
Section: Introductionmentioning
confidence: 99%